The Relationship Between Work Posture and Musculoskeletal Disorders (MSDS) in Nurses Working in Inpatient Wards - Sipayung, Selamat; Sari Desi Esta Ulina Sitepu (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
As a healthcare worker, a nurse is required to perform their job effectively while providing patient care. In carrying out their work, nurses are often faced with task that involve repetitive, unnatural posturey. This affects nurses performance when providing nursing care to patients. This study aims to examine the relationship between work posture and musculoskeletal disorders among nurses working in the inpatient ward of H. Amri Tambunan Lubuk Pakam Regional Hospital. This research was an analytical study using a cross sectional approach. The sample size was 40 people. The results of the previous study showed that work posture was significantly associated with musculoskeletal disorders among nurses .The results of the statistical test using the chi-square test showed a p value of 0,000 (p < 0,05). Based on these results, researchers can conclude that non-ergonomic body postures that occur in nurses while performing their work are associated with the risk of experiencing musculoskeletal disorders. Therefore, through the resuts of this study, the researcher would like to suggest that nurses on duty do stretching movements after carrying out work activities for along time.